SLAP Is a Negative Regulator of FcεRI Receptor-Mediated Signaling and Allergic Response - Sharma, Namit; Ponce, Marta; Kaul, Savar; Pan, Zhongda; Berry, Donna M.; Eiwegger, Thomas; McGlade, Catherine J. (Frontiers in Immunology, 2019)
Binding of antigen to IgE-high affinity FcεRI complexes on mast cells and basophils results in the release of preformed mediators such as histamine and de novo synthesis of cytokines causing allergic reactions. Src-like adapter protein (SLAP) functions co-operatively with c-Cbl to negatively regulate signaling downstream of the T cell receptor, B cell receptor, and receptor tyrosine kinases (RTK). Here, we investigated the role of SLAP in FcεRI-mediated mast cell signaling, using bone marrow derived mast cells (BMMCs) from SLAP knock out (SLAP KO) mice. Mature SLAP-KO BMMCs displayed significantly enhanced antigen induced degranulation and synthesis of IL-6, TNFα, and MCP-1 compared to wild type (WT) BMMCs. In addition, SLAP KO mice displayed an enhanced passive cutaneous anaphylaxis response. In agreement with a negative regulatory role, SLAP KO BMMCs showed enhanced FcεRI-mediated signaling to downstream effector kinases, Syk, Erk, and Akt. Recombinant GST-SLAP protein binds to the FcεRIβ chain and to the Cbl-b in mast cell lysates, suggesting a role in FcεRI down regulation. In addition, the ubiquitination of FcεRIγ chain and antigen mediated down regulation of FcεRI is impaired in SLAP KO BMMCs compared to the wild type. In line with these findings, stimulation of peripheral blood human basophils with FcεRIα antibody, or a clinically relevant allergen, resulted in increased SLAP expression. Together, these results indicate that SLAP is a dynamic regulator of IgE-FcεRI signaling, limiting allergic responses.